2013
DOI: 10.1158/1940-6207.capr-13-0015
|View full text |Cite
|
Sign up to set email alerts
|

Raw Garlic Consumption as a Protective Factor for Lung Cancer, a Population-Based Case–Control Study in a Chinese Population

Abstract: Protective effect of garlic on the development of cancer has been reported in vitro and in vivo experimental studies, however, few human epidemiological studies have evaluated the relationship. A population-based case-control study has been conducted in a Chinese population from 2003 to 2010, with the aim to explore the association between raw garlic consumption and lung cancer. Epidemiological data were collected by face-to-face interviews using a standard questionnaire among 1,424 lung cancer cases and 4,543… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
0
40
2
Order By: Relevance
“…The existing epidemiological evidence of the association between garlic and lung cancer (Table 1) is limited and inconsistent (21, 31-35). Review of previous literature indicates that raw/cooked garlic rather than a more processed form (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The existing epidemiological evidence of the association between garlic and lung cancer (Table 1) is limited and inconsistent (21, 31-35). Review of previous literature indicates that raw/cooked garlic rather than a more processed form (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifi c analyses for onion, garlic, leek, Chinese chive, scallion, garlic stalk and Welsh onion yielded similar results, except for onion leaf. In a population-based case-control study conducted in a Chinese population from 2003 to 2010, after adjusting for potential confounding factors, raw garlic consumption of two times or more per week was found to be inversely associated with lung cancer (odds ratio (OR) = 0.56) with a monotonic dose-response relationship (Jin et al 2013 ).…”
Section: Epidemiological/meta-analytical/ Review Studiesmentioning
confidence: 99%
“…Garlic is rich in sulfur-containing compounds (allicin), and contains flavonoids, selenium, and arginine which are all beneficial to health [89]. Several studies have shown an inverse correlation between daily garlic intake and cancer risk [9091]. Increased garlic intake is known to reduce the risk of stomach, esophageal, breast, pancreatic, and skin cancers [9093].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an inverse correlation between daily garlic intake and cancer risk [9091]. Increased garlic intake is known to reduce the risk of stomach, esophageal, breast, pancreatic, and skin cancers [9093]. Taylor et al first reported the anti-metastatic effect of garlic sulfur (ajoene) compounds [94].…”
Section: Introductionmentioning
confidence: 99%